2019
DOI: 10.1182/blood.2018892752
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of adenosine deaminase 2 triggers adenosine-mediated NETosis and TNF production in patients with DADA2

Abstract: Reduction of adenosine deaminase 2 (ADA2) activity due to autosomal-recessive loss-of-function mutations in the ADA2 gene (previously known as CECR1) results in a systemic vasculitis known as deficiency of ADA2 (DADA2). Neutrophils and a subset of neutrophils known as low-density granulocytes (LDGs) have been implicated in the pathogenesis of vasculitis, at least in part, through the formation of neutrophil extracellular traps (NETs). The study objective was to determine whether neutrophils and NETs play a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 53 publications
1
99
0
1
Order By: Relevance
“…NET is composed of a decondensed chromatin meshwork imbedded with granule proteins with anti-microbial properties. NET may also work as a physical path for immune cell migration to the inflammatory site ( 34 ). Neutrophil function is impaired in both animal models and humans with aging.…”
Section: Physiology Of Immunosenescence and Inflamm-agingmentioning
confidence: 99%
“…NET is composed of a decondensed chromatin meshwork imbedded with granule proteins with anti-microbial properties. NET may also work as a physical path for immune cell migration to the inflammatory site ( 34 ). Neutrophil function is impaired in both animal models and humans with aging.…”
Section: Physiology Of Immunosenescence and Inflamm-agingmentioning
confidence: 99%
“…This is particularly relevant for infections and other pathological processes that stimulate the formation of neutrophil extracellular traps (NETs), a unique form of cell death in which decondensed chromatin is released into the extracellular environment by activated neutrophils. A recent study reported enhanced NETosis in cells from DADA2 patients, which was linked to increased Ado signaling via adenosine receptors expressed on neutrophils ( 35 ). Thus, it is likely that increased NETosis, subsequent release of cellular DNA coupled, and dysregulated dAdo metabolism in ADA2 patients could synergize to drive innate cytokine responses in DADA2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported enhanced NETosis in cells from DADA2 patients, which was linked to increased Ado signaling via adenosine receptors expressed on neutrophils (35). Thus, it is likely that increased NETosis, subsequent release of cellular DNA coupled, and dysregulated dAdo metabolism in ADA2 patients could synergize to drive innate cytokine responses in DADA2 patients.…”
Section: Extrinsic Sensing Of Dna Danger Signalsmentioning
confidence: 99%
“…Deficiency of adenosine deaminase type 2 (DADA2) is an autosomal recessive monogenic AID caused by ADA2 (formerly known as CECR1) mutations and was first described in 2014 in patients with mild immune deficiency, systemic inflammation, and central nervous system vasculopathy (20). ADA2 deficiency leads to accumulation of adenosine, which then activates neutrophils and dysregulates macrophage differentiation to cause inflammation, damage and fibrosis of many tissues (21). We diagnosed five patients and the median age of onset was 3.2 years old.…”
Section: Non-inflammasome Related Conditionsmentioning
confidence: 99%